PEMANFAATAN RUMPUT LAUT SEBAGAI PEMACU PERTUMBUHAN DAN METAMORFOSIS KECEBONG KATAK BENGGALA, Rana catesbeiana Shaw - A.B. S usanto; A.M. Hariati; Daniar Daniar (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2007)
This research had been designed using fiber to test different pellet feed on giant Bullfrog, Rana catesbeiana. The investigation aimed to evaluate pellet feed formulated with different fortifi• cation ofseaweed on the growth and metamorphosis ofgiant bullfrog tadpole. The seaweed was then added in to formulated diet with different dosage of 0.0; 5.0; I 0.0; 15.0% of the diet. The result pellet were given to tadpole as treatment with 3 replications for each treatment. All tadpole received 7-10 %bw/day ofration given twice each day. Every week biomass of the tadpole in each fiber was measured to estimate the growth and adjusting new ration offeed. The same time metamorphosis level V.'aS monitored. Water quality parameters measured were tem• perature, pH, dissolved oxygen (DO), and total NH4-N. The experiment lasted for 4 weeks (28 days). The result can be concluded that pellet added with extracted seaweed would result higher metamorphosis level but not for growth rate.